Pengembangan Buku Penuntun Praktikum Sistem Organisasi Kehidupan dengan Model Argument-Driven Inquiry (ADI) - Wahyu Dwi Lestari; Neni Hasnunidah; Rini Rita T. Marpaung (Universitas Lampung, 2018)
This research aimed to describe the validity and practicality of life organization systems practical guidebook which was developed by ADI model. The researchs design was R D with 4-D model covered define, design, develope, and disseminate, but disseminate stage was not done. Data analysis used qualitative descriptive. The practical guidebook was made by an interesting cover. Each practical guidebook consisted; practicals title, theoretical base, objectives, research questions, tools, materials, work steps, argumentation scheme, argumentation sessions and reports. Expert and practitioner validation results showed that the valid with category